Essential mathematics testmaker plus! (Cambridge University Press, 2001)
Essential Mathematics Testmaker Plus! VCE contains 50 sets of questions covering the course requirements for Mathematics Methods Units 1–4, Advanced General Mathematics and Specialist Mathematics. The sets can be used to generate tests, worksheets or assignments on single or mixed topics. The CD-ROM is compatible with PCs and Macs.